If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1(x + -2) = 15 Reorder the terms: 1(-2 + x) = 15 (-2 * 1 + x * 1) = 15 (-2 + 1x) = 15 Solving -2 + 1x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 1x = 15 + 2 Combine like terms: -2 + 2 = 0 0 + 1x = 15 + 2 1x = 15 + 2 Combine like terms: 15 + 2 = 17 1x = 17 Divide each side by '1'. x = 17 Simplifying x = 17
| 3m^3+15m^2+18m=0 | | 2b+38=5b-4 | | 2(x-16)=25y+21 | | 3x-1=80 | | 4x^3-9x^2+2x-1=0 | | 30x+450+40x+1000=25 | | 10+.125Q=42-.125Q | | 4x+32=4x+12+20 | | (5/3)-(9x/7)=7/4 | | -2/8-2x/-3 | | 6(x-3)-3(x-2)=4(3-x)+5 | | 2(3x-2)=5-(2x+1) | | (40/20+x)=1/2 | | 40/20+x=1/2 | | 0=2x+x^2 | | x^3+13x-85=31 | | 6x+(10x+12)=18x-3 | | (x+12)+6x=9x-7 | | 2x+(6x-7)=5x | | 5x-2x=6x-7 | | 7x+(8x-8)=10x+5 | | 7x+(8x-8)=10x-5 | | 3+(x-1)=2x-1 | | 3+(x+5)=4x-4 | | 2x+(x-1)=4x-5 | | 3(4a-7)= | | 10x+(8x+12)=19x+10 | | 2x+18=4x-2 | | 8x+16=14x-14 | | 7a/2=15 | | 42-0.125Q=10+.075Q | | 2W^2+8W-42-W^2-7W-198=0 |